Holistic performance analysis and turbine-induced damping for an OWC wave energy converter. (January 2016) - López, I.; Pereiras, B.; Castro, F.; Iglesias, G.
Abstract: Although oscillating water column (OWC) systems are one of the most studied types of wave energy converter, developing a method for selecting the optimum turbine for an OWC at a given site—i.e., subjected to a particular wave climate—remains a current research topic. The objective of this work is to develop and apply a methodology for determining the optimum turbine-induced damping, i.e., that which maximises the performance of the conversion from wave to pneumatic energy, in an OWC equipped with a self-rectifying impulse turbine. The turbine can then be dimensioned to achieve this damping level. Illustrated through a case study, this method adopts a holistic approach encompassing the site-specific wave climate variability. A validated RANS-VOF model is implemented to compute the performance of the OWC for a range of damping coefficients (corresponding to different turbines) and wave conditions, selected based on their energy content and weighted by their occurrence at the site. In this manner, the pneumatic power matrices corresponding to different values of turbine-induced damping are computed, and the optimum damping accounting for the wave climate variability is determined. We find that this methodology may lead to a significant improvement in the annual energy output of the OWC chamber. Highlights: We present a method to select the optimum turbine-induced damping for an OWC. The OWC performance is assessed by means of a validated RANS-VOF model. A range of damping levels and representative wave conditions are considered. The turbine can be dimensioned based on the optimum damping level given by method. The case study shows that the method can increase the energy output by up to 46%.